Achievements in surgical treatment for colorectal liver metastases from 2000 until 2020: Dosežki kirurškega zdravljenja bolnikov z jetrnimi zasevki raka debelega črevesa in danke od 2000 do 2020 - Plahuta, Irena; Magdalenić, Tomislav; Turk, Špela; Potrč, Stojan; Ivanecz, Arpad (Acta Medico-Biotechnica, 2022)
Purpose: Colorectal cancer represents the third most frequently occurring malignant disease worldwide that most often disseminates into the liver. The present report describes the treatment possibilities and results of a surgical approach to treat colorectal liver metastases (CLM).Methods: A retrospective review of a prospectively maintained database of patients who underwent surgical treatment for CLM at the Clinical Department of Abdominal and General Surgery of University Medical Centre Maribor in Slovenia was performed. The study was based on the intention-to-treat principle. All procedures, redo procedures, morbidity, and survival were analyzed.Results: The study covered the period between January 2000 and December 2020, during which 631 surgical liver procedures were performed. A total of 352 (74.4%) patients underwent a single procedure, and 121 (25.6%) patients had more than one procedure. The largest portion of surgeries consisted of 541 (85.7%) liver resections (389 minor and 152 major). Radiofrequency ablation was performed in 61 (9.7%) cases and exploration in 29 (4.6%) cases. There were 138 (21.9%) redo procedures. A major morbidity (Clavien-Dindo grade ≥ 3a) was present in 84 (13.3%) cases. The 90-day mortality was 3.8%. In cases with a clinical risk score of 0, the median survival time was 69 months and 5- and 10-year overall survival was 57% and 38%, respectively.Conclusion: The complete surgical removal of metastases accompanied by favorable prognostic factors offers long-term survival in CLM patients.
Keywords: colorectal cancer, liver metastases, hepatectomy, survival